2002
DOI: 10.1007/pl00000300
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cells stimulate fibroblast-mediated contraction of three dimensional collagen gels in co-culture

Abstract: The present study shows that RBC can interact with mesenchymal cells in vitro. The ability of RBC to modulate fibroblast-mediated contraction in vitro, might therefore be an important mechanism regulating repair processes after injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 26 publications
0
16
2
Order By: Relevance
“…In the current study, contraction over time was suppressed in samples with physiologic and higher erythrocyte concentrations over 21 days. This is in contrast to another study by Fredriksson et al17 which showed an increase in contraction in fibroblast‐containing collagen gels with addition of erythrocytes in a time and concentration‐dependent manner. Significant increase was shown compared to gels without erythrocytes on all days between 1 and 5, and the augmentation was dependent on the number of erythrocytes added.…”
Section: Discussioncontrasting
confidence: 99%
“…In the current study, contraction over time was suppressed in samples with physiologic and higher erythrocyte concentrations over 21 days. This is in contrast to another study by Fredriksson et al17 which showed an increase in contraction in fibroblast‐containing collagen gels with addition of erythrocytes in a time and concentration‐dependent manner. Significant increase was shown compared to gels without erythrocytes on all days between 1 and 5, and the augmentation was dependent on the number of erythrocytes added.…”
Section: Discussioncontrasting
confidence: 99%
“…These mediators can also be released from the RBC, indicating a role for RBC in the regulation of inflammation (8,9,12,33,53). In line with these data, we have recently demonstrated that RBC can stimulate fibroblast-mediated collagen gel contraction in a time-and concentration-dependent manner and that coculture results in increased release of fibronectin (16). We also showed that RBC can stimulate fibroblast secretion of IL-8 and increase neutrophil migration in vitro (19).…”
mentioning
confidence: 68%
“…Others have shown that RBC can induce fibrosis in an animal model (27), and in previous studies we have demonstrated that both whole RBC and cell-free RBC-CM have the capacity to stimulate fibroblast-mediated collagen gel contraction (16) and fibroblast secretion of IL-8 (19). In the present study we show that both RBC and RBC-CM can induce MMP secretion and activity from human lung fibroblasts, indicating a role of intact RBC as well as soluble factors released.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…[15][16][17][18][19][20][21] Fibroblasts naturally contract the extracellular matrix (ECM) to close a wound, and, when placed in a collagen gel, respond in a similar fashion and contract the gel. Another in vitro model of airway involves culturing epithelial cells as monolayer on a membrane and fibroblasts as a monolayer a fixed distance away separated by culture medium.…”
Section: )mentioning
confidence: 99%